BIOEKOLOGI AGROFORESTRY KOPI: TUTUPAN VEGETASI DAN POLA TUMBUHAN PENYUSUN AGROFORESTRY KOPI (Coffea sp.) DI KECAMATAN PENGARON KABUPATEN BANJAR KALIMANTAN SELATAN - Kissinger Kissinger; Rina Muhayah Noor Pitri (Universitas Lambung Mangkurat, 2017)
Coffee agroforestry is a pattern of coffee cultivation mixed with other crops of one and two species, as well as more plant species. The objective of this research is to characterize vegetation cover type around coffee agroforestry and plant pattern of coffee agroforestry. The method used in data collection is by design of field observation and focal plant species for data collection about vegetation from coffee agroforestry. Data were analyzed by the descriptive method through narration from the result of data interpretation in tabulation matrix. There are 5 types of vegetation cover in the study sites: rubber plantation, mixed garden/yard garden, open field and shrubs, rice fields and cultivation fields, natural vegetation in riparian and swamp. Coffee crops are widely grown in the form of agroforestry mixed garden and yard garden. Some fruits planted with coffee are dominated by langsat (Lansium domesticum), cempedak (Artocarpus champeden), coconut (Cocos nucifera), and banana (Musa spp.). Based on the bioecological perspective, the diversity of flora contained in coffee agroforestry is very important in maintaining the stability of ecosystems, soil and water conservation, the conservation of animals on the surface and underground of the soil.